Strategies Of Housewives in Strengthening the Economy Through Environmental Utilization for Family Education - Haryu, Haryu; Hatta, Hatta; Huroniyah, Fuadatul; Zuhri, Moh. Ali Syaifudin; Sholeh, Farhanudin (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study explores strategies employed by housewives in four sub-districts of Jember Regency Sumberbaru, Tanggul, Rambipuji, and Ledokombo to strengthen the family economy through environmental resource utilization. Using a qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation, then analyzed through data reduction, presentation, and conclusion drawing. Source and method triangulation ensured the validity of findings. The results indicate that utilizing yard land for household agriculture, circular economy-based waste management, and environment-based small business development significantly enhance family income, environmental sustainability, and family education. Home gardening improves food security and provides additional income, while household waste management, including recycling and composting, generates economic value and mitigates environmental impact. Moreover, small businesses utilizing natural products foster entrepreneurship while promoting sustainability. This study contributes to the literature on household economy, circular economy, and sustainability-based entrepreneurship within rural Indonesia. The findings highlight the necessity of a holistic approach in family economic planning, integrating economic, social, and educational dimensions. These insights have practical implications for policies supporting sustainable rural development, emphasizing economic resilience, environmental stewardship, and family education